2018
DOI: 10.3892/or.2018.6252
|View full text |Cite|
|
Sign up to set email alerts
|

Yap regulates gastric cancer survival and migration via SIRT1/Mfn2/mitophagy

Abstract: Gastric cancer is the fifth most common cancer worldwide and Hippo-Yap is the novel signaling pathway which plays an important role in gastric cancer tumor development and progression. However, little insight is available to date regarding the specific role of Yes-associated protein (Yap) in gastric cancer. In the present study, we identified the mechanism through which Yap sustains gastric cancer viability and migration. Yap was greatly upregulated in gastric cancer cells and its expression promoted cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 53 publications
2
69
0
Order By: Relevance
“…The similar results could also be observed in the study of Zhou and his colleagues [28]. Moreover, Yan showed that YAP acted as a tumor promoter in gastric cancer, and involved in the survival and migration of GC cells through the activation of the SIRT1/Mfn2/mitochondrial autophagy axis [29]. However, there are still inconsistent results published.…”
Section: Discussionsupporting
confidence: 78%
“…The similar results could also be observed in the study of Zhou and his colleagues [28]. Moreover, Yan showed that YAP acted as a tumor promoter in gastric cancer, and involved in the survival and migration of GC cells through the activation of the SIRT1/Mfn2/mitochondrial autophagy axis [29]. However, there are still inconsistent results published.…”
Section: Discussionsupporting
confidence: 78%
“…Our previous studies demonstrated that SIRT1 has a protective role in IVDD 31,32 . Furthermore, several studies revealed that SIRT1 plays a key role in mitophagy and apoptosis in a variety of aging-related diseases via SIRT1-Parkin-Mitohphagy pathway [33][34][35][36][37] . In present study, we showed that circERCC2 regulated the expression of SIRT1 by sponging miR-182-5p.…”
Section: Discussionmentioning
confidence: 99%
“…This affords F-actin a central position within cellular response networks. Based on previous studies, F-actin dysregulation is associated with gastric cancer migration inhibition via sirtuin 1/mitofusin 2-mediated mitophagy ( 12 , 13 ). Furthermore, F-actin downregulation contributes to rectal cancer mitochondrial apoptosis via activation of the c-Jun N-terminal kinase (JNK)-dynamin-related protein 1-mitochondrial fission-HtrA serine peptidase 2/Omi axis ( 14 ).…”
Section: Introductionmentioning
confidence: 99%